Pharmacokinetics of antiretroviral drugs in infancy - Helen McIlleron; Hermien Gous (AOSIS, 2009)
Infancy (from birth until 1 year of age) is a time of rapid changes within the body of a child. These changes affect pharmacokinetics in many ways. The CHER study1 showed that early antiretroviral treatment reduces mortality and disease progression amongst infants acquiring HIV infection before 12 weeks of age. As a result the World Health Organization has recently revised treatment initiation recommendations in children less than one year of age: all infants under 12 months of age with confirmed HIV infection should be started on antiretroviral therapy, irrespective of clinical or immunological stage2. Dosing in infants is challenging because drug concentrations are highly variable, there is frequently scant pharmacokinetic information in young children, and few suitable drug formulations are available. Furthermore, adherence to treatment is reliant on the caregiver, rather than the patient. Peri- and postnatal HIV transmission are reduced by maternal highly active antiretroviral treatment (HAART). However, the benefits and risks to breast fed infants of exposure to maternal antiretroviral drugs during lactation are poorly understood. In this article we review the pharmacokinetics of antiretroviral drugs relevant to South African infants, and highlight some of the challenges to delivering antiretroviral treatment in safe and effective doses.